The Influence of Personal Characteristics, Competence, and Auditor Experience on Audit Quality in the Government Sector in Jakarta - Satria Aristawa; Muhyarsyah Muhyarsyah (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
This This study aims to examine the influence of professional skepticism, audit knowledge, and auditor experience in dealing with audit complexity on audit quality among auditors engaged in public sector audits in Jakarta. The issue of audit quality in Indonesia remains a serious concern, as evidenced by various audit findings and violations reported by regulatory bodies. This research employs a quantitative approach using a survey method. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique, which includes (1) testing the measurement model (outer model) to assess convergent validity, discriminant validity, and construct reliability, and (2) testing the structural model (inner model) to evaluate the relationships among variables and to test the research hypotheses. The results of the hypothesis testing show that professional skepticism (β = 0.384), audit knowledge (β = 0.275), and auditor experience (β = 0.403) have positive and significant effects on audit quality, with auditor experience being the most dominant factor. The study concludes that enhancing audit quality can be achieved by strengthening auditors’ personal characteristics, technical knowledge, and practical experience through continuous training and professional development programs.